2021
DOI: 10.1111/cag.12735
|View full text |Cite
|
Sign up to set email alerts
|

An ecological systems analysis of food access barriers and coping strategies adopted by older adults in Ghana

Abstract: The barriers to accessing food and strategies adopted by older adults in Ghana are distinct but interconnected and are produced by both individual and structural factors.• An ecological systems theory offers a useful perspective for understanding the food access experiences of older adults in low-income contexts. • Addressing the food needs of older people will require a multilevel, comprehensive approach that targets the individual and broader human environment.The 2030 Agenda for Sustainable Development comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…Whereas association between psychological disorders [31], sleep quality [32], mental distress [33], financial services [34] and food insecurity have been previously examined quantitatively among older adults in Ghana, Amoak et al [35] investigated the link between household food insecurity and self-rated oral health in Ghana. Further, Braimah and Rosenberg [36] qualitatively investigated food access barriers and coping strategies adopted by older adults in Ghana. The study found that barriers to access to food in old age include functional impairment and poor health, poverty, insufficient social support, poor control over household resources, policy neglect, low crop yields, and sociocultural values [36].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Whereas association between psychological disorders [31], sleep quality [32], mental distress [33], financial services [34] and food insecurity have been previously examined quantitatively among older adults in Ghana, Amoak et al [35] investigated the link between household food insecurity and self-rated oral health in Ghana. Further, Braimah and Rosenberg [36] qualitatively investigated food access barriers and coping strategies adopted by older adults in Ghana. The study found that barriers to access to food in old age include functional impairment and poor health, poverty, insufficient social support, poor control over household resources, policy neglect, low crop yields, and sociocultural values [36].…”
Section: Introductionmentioning
confidence: 99%
“…Further, Braimah and Rosenberg [36] qualitatively investigated food access barriers and coping strategies adopted by older adults in Ghana. The study found that barriers to access to food in old age include functional impairment and poor health, poverty, insufficient social support, poor control over household resources, policy neglect, low crop yields, and sociocultural values [36]. However, what remains unclear is the linkage between FSS and HSB during illness in old age.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the three regions where rice is predominantly produced in Ghana, are the Eastern Region, Northern Region and Ashanti Region (Cadger et al, 2016:35;Muhammed, Tela, and Wahab, 2022). The study was conducted in the Eastern Region of Ghana because rice farmers in this region are estimated to contribute more than half of all rice produced in Ghana for local consumption (Braimah, and Rosenberg, 2022;Donkor, Matthews and Ogundeji, 2018:157). The three ricefarming communities that dominate rice production in this region are: Akuse, Asutsuare, and Kpong.…”
Section: Introductionmentioning
confidence: 99%
“…Despite, the critical importance of rice farming, rice yield has been slowing down, especially among smallholder farmers in Ghana (Braimah, and Rosenberg, 2022;Moglia et al, 2018:85). For instance, the average rice yields potential is 10t/ha; however, the global average rice yield has hovered around 7-8 t/ha, with average yield from developing countries hovering around 4-5t/ha (Moglia et al, 2018:86).…”
Section: Introductionmentioning
confidence: 99%